2014
DOI: 10.1123/jsep.2013-0115
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Level Moderates Executive Control Disruption During Exercise Regardless of Age

Abstract: The purpose of this study was to assess the effects of exercise intensity, age, and fitness levels on executive and nonexecutive cognitive tasks during exercise. Participants completed a computerized modified-Stroop task (including denomination, inhibition, and switching conditions) while pedaling on a cycle ergometer at 40%, 60%, and 80% of peak power output (PPO). We showed that a bout of moderate-intensity (60% PPO) to high-intensity (80% PPO) exercise was associated with deleterious performance in the exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…The results presented in the literature regarding the acute effect of different exercise intensities on RT and error rates are contradictory The decrease in accuracy found in the present study is in line with a number of studies [ 41 , 44 46 ]. On the other hand, Stroop interference in terms of RT did not change throughout the session, which also corroborates previous studies [ 44 , 45 ]. Nonetheless, meta-analyses have shown a small increase in Stroop RT at high exercise intensities [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results presented in the literature regarding the acute effect of different exercise intensities on RT and error rates are contradictory The decrease in accuracy found in the present study is in line with a number of studies [ 41 , 44 46 ]. On the other hand, Stroop interference in terms of RT did not change throughout the session, which also corroborates previous studies [ 44 , 45 ]. Nonetheless, meta-analyses have shown a small increase in Stroop RT at high exercise intensities [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, this would imply that older adults with a sedentary lifestyle who participate in regular exercise training would experience greater benefits in terms of EF. This finding supports previous reviews which suggested that exercise in those with lower physical fitness levels might be more beneficial to EF as compared to such activity in those with high physical fitness levels [ 59 , 60 ]. However, while the ESs for sedentary and fit participants were significantly different, the findings of this review suggested a positive effect on EF regardless of fitness levels.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the current empirical evidence regarding age-related difference is somewhat contradictory. Dimitrova et al [ 67 ] reported larger cognitive gains in older adults, but others found no such difference [ 68 , 69 , 70 ]. Nevertheless, it is hard to directly compares these studies since they differed in terms of whether they included a non-exercise condition (Dimitrova et al did not), exercise modes (e.g., Hsieh et al adopted resistance exercise whereas others adopted aerobic exercise), timing of cognitive assessments (e.g., Labelle et al assessed in-exercise cognitive performance while the others assessed post-exercise performance), and cognitive tasks (e.g., while Kamijo et al employed the Flanker task and Hsieh et al used the working memory task, the Stroop test was used by others).…”
Section: Discussionmentioning
confidence: 99%